Adolescent sexual offenders grown up - Sipe, Ron (Criminal justice and behavior, 1998)
The objective of this study was to compare the recidivism rates of juvenile sexual offenders with those of other juvenile offenders once they became young adults. The authors found that the juveniles adjudicated for a sexual offense had a significantly higher rate of recidivism for sexual offenses as adults than did the comparison group, but rearrest rates for sexual offenses were low in both groups. The juvenile nonsexual offenders had higher rates of adult recidivism for all other types of offenses